Learning and memory with neuropathic pain: impact of old age and progranulin deficiency - Albuquerque, Boris; Häussler, Annett; Vannoni, Elisabetta; Wolfer, David P.; Tegeder, Irmgard (Frontiers in Behavioral Neuroscience, 2013)
Persistent neuropathic pain is a frequent consequence of peripheral nerve injuries, particularly in the elderly. Using the IntelliCage we studied if a sciatic nerve injury obstructed learning and memory in young and aged mice, each in wild type and progranulin deficient mice, which develop premature signs of brain aging and are more susceptible to nerve injury evoked nociceptive hypersensitivity and hence allow to assess a potential mutual aggravation of pain and old age. Both young and aged mice developed long-term nerve injury-evoked hyperalgesia and allodynia but, in both genotypes, only aged mice with neuropathic pain showed high error rates in place avoidance acquisition tasks. Once learnt however, aged mice with neuropathic pain maintained the aversive memory longer, i.e. the extinction was significantly slowed. In addition, nerve injury in progranulin deficient mice impaired the learning of spatial sequences of awarded places, particularly in aged mice, whereas easy place preference learning was not affected by nerve injury or progranulin deficiency. The sequencing task required a discrimination of clockwise and anti-clockwise sequences and spatial flexibility to re-learn a novel sequence. The loss of spatial flexibility did not occur in sham operated mice, i.e. was a consequence of nerve injury and suggests that neuropathic pain accelerates manifestations of old age and progranulin deficiency. Neuropathic pain at old age, irrespective of the genotype, resulted in a long maintenance of aversive memory suggesting a negative alliance and possibly mutual aggravation of chronic neuropathic pain and aversive memory at old age.